Differences in Sperm Motility Based on Sleep Quality in Infertilized Men at RSKIA Sadewa - Daniel Pradana Andrian Wicaksono; Oscar Gilang Purnajati; Seso Sulijaya Suyono (Indonesian Andrology and Biomedical Journal, 2025)
Background : Infertility is a significant reproductive health issue, with a global prevalence of 8–12% among couples of reproductive age. One contributing factor is decreased sperm quality, including sperm motility. Poor sleep quality is suspected to affect sperm motility through hormonal disruptions and oxidative stress; however, research in Indonesia remains limited. Objective : This study aims to determine the differences in sperm motility based on sleep quality in infertile men at RSKIA Sadewa Yogyakarta. Methods : This study employed an analytical observational design with a cross-sectional approach. The sample consisted of 60 infertile men aged 20–45 years who met the inclusion criteria. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI), while sperm motility data were obtained from medical records. Data were analyzed using the independent sample t-test and One-Way Anova. Results : The results showed no significant difference in sperm motility between the good and poor sleep quality groups (p 0.374). The average sperm motility in the good sleep quality group was 48.43%, while in the poor sleep quality group, it was 43.90%. Confounding variables such as age, IMT, and smoking habits also did not show a significant effect on sperm motility. Conclusion : Sperm motility in infertile men at RSKIA Sadewa who had good sleep quality was not significantly different compared to those with poor sleep quality. Keywords : sleep quality, sperm motility, male infertility, PSQI, reproductive health